2017
DOI: 10.4028/www.scientific.net/kem.743.58
|View full text |Cite
|
Sign up to set email alerts
|

Contact Melting Mechanism in the Cu-Ti System

Abstract: A mechanism for the formation of the interaction zone at the interlayer interface of the explosively welded Cu-Ti system composite is proposed and experimentally proved; the heat treatment was performed under a contact melting regime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 4 publications
(4 reference statements)
0
8
0
Order By: Relevance
“…It is a mixture of Ti2Ni(Cu), TiNi(Cu), and Ti2Cu(Ni) intermetallics (Figure 11, Table 12). Changing the region of the eutectic structure formation and its phase composition allowed us to conclude that the CM process was ongoing according to a mechanism similar to that described in [22,24]. Metallographic studies of IZ after heat treatment at 850 • C, 50 h + 950 • C, 1 min showed that on the side of the CuNi45 alloy, interlayers of TiNi 3 (Cu), TiCuNi, TiNi(Cu) and Ti 2 Ni(Cu) were formed, and on the side of titanium VT1-0 solid solution based on αTi was formed (Figure 10, Table 11).…”
Section: Diffusion Processes In Vt1-0 + Cuni45 Compositementioning
confidence: 89%
See 4 more Smart Citations
“…It is a mixture of Ti2Ni(Cu), TiNi(Cu), and Ti2Cu(Ni) intermetallics (Figure 11, Table 12). Changing the region of the eutectic structure formation and its phase composition allowed us to conclude that the CM process was ongoing according to a mechanism similar to that described in [22,24]. Metallographic studies of IZ after heat treatment at 850 • C, 50 h + 950 • C, 1 min showed that on the side of the CuNi45 alloy, interlayers of TiNi 3 (Cu), TiCuNi, TiNi(Cu) and Ti 2 Ni(Cu) were formed, and on the side of titanium VT1-0 solid solution based on αTi was formed (Figure 10, Table 11).…”
Section: Diffusion Processes In Vt1-0 + Cuni45 Compositementioning
confidence: 89%
“…It is a mixture of Ti 2 Ni(Cu), TiNi(Cu), and Ti 2 Cu(Ni) intermetallics (Figure 11, Table 12). Changing the region of the eutectic structure formation and its phase composition allowed us to conclude that the CM process was ongoing according to a mechanism similar to that described in [22,24]. In accordance with [22,24], an increase in the nickel content in β-Ti to a certain critical concentration led to the "blocking" of its individual small regions by "partitions" of nickel atoms and the formation of nano-sized volumes (clusters) on which size effect of melting was realized [21].…”
Section: Diffusion Processes In Vt1-0 + Cuni45 Compositementioning
confidence: 89%
See 3 more Smart Citations